Relation between Roots and Method of Irrigation in Dry Tracts of the Punjab - Deogun, P. N. (Indian Forester, 1943)
The note deals with: (i) a general description of the irrigated plantations of the Punjab, (ii) the development of irrigation system and its effect on growth of plantations, (iii) observations made on growth of sissu in relation to its root system, (iv) experiments carried out to help sissu to produce a deep root system, and (v) disadvantages of shallow irrigation and advantages of having deep-rooted crops.